2021
DOI: 10.1016/j.appet.2020.104977
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative exploration of the impact of COVID-19 on individuals with eating disorders in the UK

Abstract: COVID-19 may have substantial impact on the mental health at a population level, but also has the potential to significantly affect those with pre-existing mental health difficulties such as eating disorders. This qualitative study explores the impact of COVID-19 and associated public health measures on adults with eating disorders within the UK. We conducted 10 in depth interviews with adults (24-38 years) with a self-reported eating disorder during lockdown. Data were analysed using an inductive thematic ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
93
0
9

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(121 citation statements)
references
References 26 publications
10
93
0
9
Order By: Relevance
“…Reasons cited for this motivation included the convenience of tele-therapy, as well as concerns related to eating disorder symptoms and being at greater risk of contracting the virus. These findings are consistent with those from Brown et al (2020), who identified that many patients displayed an increased drive for recovery in response to the stressors experienced during COVID-19. During treatment, high levels of motivation can be harnessed to encourage behavior change and help patients achieve their recovery goals.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Reasons cited for this motivation included the convenience of tele-therapy, as well as concerns related to eating disorder symptoms and being at greater risk of contracting the virus. These findings are consistent with those from Brown et al (2020), who identified that many patients displayed an increased drive for recovery in response to the stressors experienced during COVID-19. During treatment, high levels of motivation can be harnessed to encourage behavior change and help patients achieve their recovery goals.…”
Section: Discussionsupporting
confidence: 90%
“…Eating disorder symptom improvement has been observed in a minority of cases (Branley-Bell & Talbot, 2020;Brown et al, 2020;Schlegl et al, 2020;Termorshuizen et al, 2020). In these studies, anywhere between 2% to 25% of patients cited positive outcomes associated with the pandemic (Branley-Bell & Talbot, 2020;Schlegl et al, 2020).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The findings of this analysis partially align with the hypotheses of Rodgers and colleagues [ 13 ], which posit that the COVID-19 pandemic worsens ED risk via limited access to care and social support networks, increased exposure to ED-specific media, and anxiety related to changing food quantity and quality. Reddit users included in this analysis frequently discussed the disruption to or cessation of ED treatment following the onset of the pandemic and struggled with limited access to both formal and informal support networks—a finding that supports the first hypothesis of Rodgers and colleagues [ 13 ] and expands on findings from a similar qualitative investigation conducted using a smaller sample of adults with self-reported ED [ 31 ]. Our findings also supported the third hypothesis of Rodgers and colleagues and suggested that changed food availability contributed to increased anxiety and ED behavior.…”
Section: Discussionsupporting
confidence: 59%
“…While this change in environment may be supportive for some, for others it is potentially distressing. [20][21] Therefore, it is imperative to understand the role of these environmental disruptions on ED and mental health (MH)-related outcomes.…”
Section: Introductionmentioning
confidence: 99%